Proceedings of the 2011 International Symposium on Software Testing and Analysis 2011
DOI: 10.1145/2001420.2001461
|View full text |Cite
|
Sign up to set email alerts
|

The use of mutation in testing experiments and its sensitivity to external threats

Abstract: Mutation analysts has emerged as a standard approach for empirical assessment of testing techniques. The test practitioners decide about cost-effectiveness of testing strategies based on the number of mutants the testing techniques detect. Though fundamental rigor to empirical software testing, the use of mutants in the absence of real-world faults has raised the concern of whether mutants and real faults exhibit similar properties. This paper revisits this important concern and disseminates interesting findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 26 publications
0
42
1
Order By: Relevance
“…Request permissions from Permissions@acm.org. real faults [1,8,27]. Our work differs from these previous studies in four main aspects.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Request permissions from Permissions@acm.org. real faults [1,8,27]. Our work differs from these previous studies in four main aspects.…”
Section: Introductionmentioning
confidence: 81%
“…Namin and Kakarla [27] later replicated the work of Andrews et al [1], used a different mutation testing tool (Proteum), and came to a different conclusion: they found that the correlation between the mutation score and the real fault detection rate for Space was weak. They also extended the work to five Java classes from the standard library, ranging from 197 to 895 lines of code.…”
Section: Studies That Explored the Relationship Between Mutants And Rmentioning
confidence: 96%
“…However, in practice mutation is sensitive to the underlying mutants that it is using. In other words, the set of the realised operators can have a major impact on both scalability [9] and effectiveness [8] of the technique. Therefore, it is mandatory to equip mutation tools with a comprehensive set of mutants that can adequately measure test thoroughness and at the same time is practical.…”
Section: Mutation Testingmentioning
confidence: 99%
“…Namin et al [21] caution that this insight is highly sensitive to external threats mentioning several influential factors that must be accounted for. In the present paper we have investigated not the detectability but the complexity of regression errors and found that the complexity of regression errors resulting from seeded faults is different from that of actual regression errors.…”
Section: Related Workmentioning
confidence: 99%
“…Since the method traverseChange is a recursive traversal algorithm, we mark the visited vertices as such (lines [14][15]. If any basic block bb transitively following c is changed, then add an edge from c to bb (lines [16][17][18][19][20][21]. If c or any transitively following basic block, transitively calls a changed method m ′ , continue traversal from the f irst basic block in the CF G ′ of m ′ (lines [23][24][25][26].…”
mentioning
confidence: 99%